Integrating Pro-Tech Learning into a Sociolinguistic Approach Through Practitioners’ Involvement for Multicultural Awareness - Rosiana, Caltira; Cahyanti, Triana Wuri (Studies in Learning and Teaching, 2025)
This research aims to enhance multicultural awareness for university students through the integration of Pro-Tech Learning in sociolinguistic instruction. A qualitative classroom action research design was employed through two instructional cycles consisting of planning, action, observation, and reflection. The participants were 19 undergraduate students of the English Language Education Department enrolled in a sociolinguistics course. Data were collected using questionnaires, classroom observations, performance-based projects, interviews, and documentation. The data were analyzed through descriptive quantitative analysis and paired-sample t-tests, supported by thematic qualitative analysis. The findings reveal a significant improvement in students’ sociolinguistic conceptual understanding, learning engagement, and technology integration after the implementation of Pro-Tech Learning. Students demonstrated stronger critical analysis of sociolinguistic phenomena, increased tolerance, and greater sensitivity toward cultural and linguistic diversity. This study concludes that integrating Pro-Tech Learning with practitioner involvement effectively bridges theoretical knowledge and real-world sociolinguistic practice, thereby fostering inclusive and multicultural-oriented learning in higher education.